Efektivitas Pelaksanaan Pendidikan Enterpreneurship (Studi Kasus di Madrasah Tsanawiyah Negeri 1 Palembang) - Arnaini; Paizaluddin (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2021)
The purpose of this study was to determine the effectiveness of the implementation of entrepreneurship education in Madrasah Tsanawiyah Negeri 1 Palembang. The research method used in this study is a qualitative method with a survey approach, namely research that takes data using interviews as the main money data collection tool. Based on the results of the research and discussion above, it can be concluded that: In the input aspect, learning materials have been effectively developed through the implementation of entrepreneurship education at MTs Negeri 1 Palembang, especially in the subject of Skills Education. In addition, existing infrastructure facilities can support the implementation of entrepreneurship education. In the process aspect, students' creative and critical thinking skills have not been optimally developed, the mentoring and mentoring process has been carried out by the coach teacher, but students are still dependent on the teacher's ideas, even though the implementation of entrepreneurship education is focused on forming students' mindsets. In the output aspect, the increase in students' creative thinking has not been seen, dependence on the teacher's ideas still occurs, while the increase in thinking patterns and the entrepreneurial spirit has gradually increased.